2010
DOI: 10.1143/jpsj.79.093703
|View full text |Cite
|
Sign up to set email alerts
|

Itinerant Electron Metamagnetism in η-Carbide-Type Compound Co3Mo3C

Abstract: We report the magnetic properties of the cobalt molybdenum -carbide-type compounds Co 3 Mo 3 C and Co 3 Mo 3 N. The magnetic susceptibility of Co 3 Mo 3 C shows a Curie-Weiss temperature dependence at high temperatures and a broad maximum at around 100 K, whereas that of Co 3 Mo 3 N shows a nearly temperature-independent enhanced Pauli paramagnetic behavior. The absence of a magnetic long-range order was confirmed by the nuclear magnetic resonance technique in both the compounds. As expected from the broad max… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2011
2011
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 24 publications
1
6
0
Order By: Relevance
“…However their detailed electronic properties remain to be investigated. Recently, a wide variety of magnetic properties of η-6 have been reported by our group [4,5,6,7] and others [8,9,10,11,12,13,14]. For example, we have found that Fe 3 Mo 3 N show a non-Fermi-liquid behavior at low temperatures [4], and proposed that, in Fe 3 Mo 3 N, long-range magnetic order is suppressed by the geometric frustration inherent to the η-carbide structure in spite of strong magnetic correlation [5].…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…However their detailed electronic properties remain to be investigated. Recently, a wide variety of magnetic properties of η-6 have been reported by our group [4,5,6,7] and others [8,9,10,11,12,13,14]. For example, we have found that Fe 3 Mo 3 N show a non-Fermi-liquid behavior at low temperatures [4], and proposed that, in Fe 3 Mo 3 N, long-range magnetic order is suppressed by the geometric frustration inherent to the η-carbide structure in spite of strong magnetic correlation [5].…”
Section: Introductionmentioning
confidence: 87%
“…Figure 4 shows field dependences of the magnetization M and its field coefficient dM/dH measured for antiferromagnetic Co 6 W 6 C at 4.2 K and up to 54 T. The magnetization of paramagnetic Co 6 Mo 6 C is also included in the figure for comparison. The magnetization of Co 6 Mo 6 C is nearly linear in contrast to the η-6 counterpart, Co 3 Mo 3 C, in which an itinerant electron metamagnetic transition was observed at ∼30 T [6]. Generally, the material which shows a hump in χ(T ) shows an itinerant electron metamagnetism and vice versa [24,25].…”
Section: Specific Heatmentioning
confidence: 97%
“…Several new topics have recently sprung from this field, e.g., iron-based η-carbide-type compounds with the stella quadrangula network, where itinerant electronic magnetism collaborates with a geometrical frustration, 1,2 and UCoGe in which superconductivity and itinerant electronic ferromagnetism coexist. [3][4][5] Collaboration between low-dimensionality and itinerant electronic magnetism is also one of the interesting topics.…”
Section: Introductionmentioning
confidence: 99%
“…Nitrides with the so-called h-carbide structure, 1 for example Fe 3 Mo 3 N and Co 3 Mo 3 N, have been the subject of many recent studies that have addressed either their mechanical properties and hardness, 2,3 their catalytic activity [4][5][6][7][8] or their electrical 9 and magnetic properties. [10][11][12][13] Our interest lies in the latter. Although an earlier study 14 reported that Fe 3 Mo 3 N is antiferromagnetic below 120 K, the most recent neutron diffraction and M€ ossbauer data 11 show convincingly that no long-range magnetic order is present at 4.5 K. The temperature dependence of the electrical resistivity and the specific heat led Waki et al to describe this compound as behaving like a non-Fermi liquid close to a ferromagnetic quantum critical point.…”
Section: Introductionmentioning
confidence: 99%
“…The isostructural compound Co 3 Mo 3 N has been described as a Pauli paramagnet, with the absence of long-range magnetic order having been proved by nuclear magnetic resonance spectroscopy. 10 A study 15 of the mixed-metal system Fe 3Àx Co x Mo 3 N revealed a large enhancement of the magnetisation of Fe 2.5 Co 0.5 Mo 3 N below 30 K in a field of 100 Oe, but no evidence for long-range magnetic order was apparent in neutron diffraction data collected at 5 K; the compound was described as a superparamagnet. It was also observed that the distribution of iron and cobalt over the two available sites in the structure was not random.…”
Section: Introductionmentioning
confidence: 99%